2021
DOI: 10.1186/s12948-021-00159-4
|View full text |Cite
|
Sign up to set email alerts
|

The potential protective role of corticosteroid therapy in patients with asthma and COPD against COVID-19

Abstract: Background The observation of patients hospitalized for coronavirus disease (COVID-19) led us to note a lower prevalence of patients affected by chronic respiratory disease, in particular asthmatic patients, compared to the general population. Therefore, the aim of this paper is to evaluate the possible protective role of corticosteroid therapy in patients with chronic lung disease, regarding the risk of contracting severe COVID-19. Main body SARS-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“… 4 In addition, some studies have suggested that the use of inhaled corticosteroids (ICS) in asthma may have a protective effect and may be contributing to a decreased risk of severe COVID-19 disease. 5 6 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 4 In addition, some studies have suggested that the use of inhaled corticosteroids (ICS) in asthma may have a protective effect and may be contributing to a decreased risk of severe COVID-19 disease. 5 6 …”
Section: Introductionmentioning
confidence: 99%
“…However, a recently published systematic review concluded that people with asthma are not at increased risk for acquiring COVID-19 compared with those without and also have similar outcomes following a COVID-19 infection compared with people without asthma 4. In addition, some studies have suggested that the use of inhaled corticosteroids (ICS) in asthma may have a protective effect and may be contributing to a decreased risk of severe COVID-19 disease 5 6…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have suggested that inhaled asthma medications' antiviral and immunomodulatory activities should also be considered 35 . In this regard, some authors have argued that inhaled corticosteroids may have a protective effect, contributing to a decreased risk of severe COVID‐19 in patients with asthma 36 . Some behavioral aspects may also have played a role in reducing the vulnerability of asthma patients to SARS‐CoV‐2 infection 37 .…”
Section: Discussionmentioning
confidence: 99%
“…35 In this regard, some authors have argued that inhaled corticosteroids may have a protective effect, contributing to a decreased risk of severe COVID-19 in patients with asthma. 36 Some behavioral aspects may also have played a role in reducing the vulnerability of asthma patients to SARS-CoV-2 infection. 37 However, it is essential to emphasize that asthma is a complex disease, and more clinical and experimental studies are needed to elucidate the mechanisms involved in the interactions between asthma and SARS-CoV-2 infection.…”
Section: Asthma Cohortmentioning
confidence: 99%
“…To date, published (mostly laboratory) studies and reviews rather suggest a potential preventive effect of pre-morbid and continued use of ICS against a hyperinflammatory response. [8][9][10] A recent study, in contrast, reported that pre-morbid ICS use in COPD was not protective and even increased risk of developing COVID-19. 11 A systematic review of more recent studies about pre-morbid and continued use of ICS found no evidence that ICS use was associated with worse outcomes, even though results and conclusions are likely confounded by different factors (ICS indication, sample size, lack of adjustment for comorbidities).…”
Section: Introductionmentioning
confidence: 94%